Aircraft Charging and its Influence on Triggered Lightning. Issue 1 (11th January 2020) - Pavan, C.; Fontanes, P.; Urbani, M.; Nguyen, N. C.; Martinez‐Sanchez, M.; Peraire, J.; Montanya, J.; Guerra‐Garcia, C.
Abstract: This paper reports on a laboratory experiment to study the effect of vehicle net charge on the inception of a positive leader from an aircraft exposed to high atmospheric electric fields. The experiment models the first stage of aircraft‐triggered lightning in which a positive leader typically develops from the vehicle and is shortly afterwards followed by a negative leader. This mechanism of lightning initiation amounts to around 90% of strikes to aircraft. Aircraft can acquire net charge levels of the order of a millicoulomb from a number of sources including corona emission, charged particles in the engine exhaust, and charge transfer by collisions with particles in the atmosphere. In addition, aircraft could potentially be artificially charged through controlled charge emission from the surface. Experiments were performed on a model aircraft with a 1m wingspan, which was suspended between two parallel electrodes in a 1.45m gap with voltage difference of a few hundred kilovolts applied across it. In this configuration, it is found that the breakdown field can vary by as much as 30% for the range of charging levels tested. The experimental results show agreement with an electrostatic model of leader initiation from aircraft, and the model indicates that the effect can be substantially stronger if additional negative charge is added to the aircraft. The results from this work suggest that flying uncharged is not optimal in terms of lightning avoidance and open up the possibility of developing risk‐reduction strategies based on net charge control. Plain Language Summary: Commercial aircraft are typically struck by lightning around once per year, and the vast majority of these events are triggered by the aircraft itself. The lightning discharge originates on the surface of the aircraft in areas with sharp edges. Whether a discharge develops is in part due to the net electric charge of the aircraft, which can be acquired both naturally or artificially. Previous work has shown that it is theoretically possible to reduce the likelihood of a lightning strike occurring by manipulating the net charge of the aircraft. In this paper, the authors perform laboratory experiments to validate this hypothesis. These experiments demonstrate that the threshold for lightning could be increased by 30% by charging the aircraft negatively, which means that an aircraft could fly safely through ambient electric fields that are around 30% higher than those of an uncharged baseline. Theoretical estimates suggest that further improvement may be possible if the aircraft were charged to a more negative state than those tested. This work gives laboratory scale experimental evidence that it is possible to reduce the frequency of lightning strikes on aircraft by manipulating their charge and encourages further investigation of the proposed lightning strike risk reduction strategy. Key Points: Aircraft‐triggered lightning is influenced by the net charge of the floating body Positive leader inception from an aircraft requires higher amplitude external fields when negatively biasing the vehicle Experimental results validate a proposed method of aircraft‐triggered lightning strike risk reduction